NEW YORK CITY INTERMEDIATE STATUS REPORT (Tufts Archival Research Center, 2007)
New York City status report for April 1985. Refers to the actions taken by the Tobacco Industry to hinder the agenda of the New York City Council Health Committee. Mentions the New York City code, which restricts smoking in public places. Criticizes code because it will prevent people from experimenting or using tobacco products in the state of New York. Describes lobbying efforts and explains coalition support, public relations and marketing.